Analysis of the Influence of TikTok Social Media and the Ease of Use of the Tokopedia Marketplace Platform on the Purchase Intention of Digital Business Students - Claudia, Ivana Ester; Christina, Kezia Dantya; Mu’awwanah, Alya Syifa; Zahirah, Nisrina; Melati, Risna; Guntara, Rangga Gelar (International Conference on Digital Business Innovation and Technology Management (ICONBIT), 2024)
The rapid development of technology and the internet has changed the way individuals access information and conduct transactions. This research examines the role of social media TikTok and the Tokopedia marketplace platform in influencing the behavior of college students who actively use the Tokopedia marketplace platform studying digital business, with a focus on how creative content can attract consumer attention. Engaging short videos on Tiktok, supported by sophisticated algorithms, present personalized information, thereby increasing user engagement and shopping behavior. The research method used is quantitative, with multiple linear regression analysis to evaluate the relationship between variables. The instrument used is Likert scale-based to measure respondents regarding various aspects of social media marketing and ease of use of the platform. It is expected that the results of the study show TikTok social media marketing has a positive and significant influence on students’ purchase intention, along with the ease of use of the Tokopedia marketplace which supports decision making in the purchasing process.